2021
DOI: 10.3390/molecules26175326
|View full text |Cite
|
Sign up to set email alerts
|

Film-Forming Spray of Water-Soluble Chitosan Containing Liposome-Coated Human Epidermal Growth Factor for Wound Healing

Abstract: Human epidermal growth factor (hEGF) has been known to have excellent wound-healing activity. However, direct application to the wound area can lead to low hEGF bioavailability due to protease enzymes or endocytosis. The use of liposomes as coatings and carriers can protect hEGF from degradation by enzymes, chemical reactions, and immune reactions. Sustained release using a matrix polymer can also keep the levels of hEGF in line with the treatment. Therefore, this study aimed to develop a film-forming spray of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Introducing montmorillonite-copper chloride into chitosan films can increase their tensile strength and elongation at break and also confer higher antibacterial activity against foodborne pathogens, further highlighting their use as a wound dressing to combat infections ( Nouri et al, 2018 ). Additionally, chitosan films containing human epidermal growth factors can protect against enzymatic hydrolysis and endocytosis and significantly accelerate the rate of wound healing in mice ( Umar et al, 2021 ). These antibacterial properties and regenerative effects of chitosan make it a suitable material for wound dressing.…”
Section: Drug Carriers Prepared Using Chitosan and Its Derivativesmentioning
confidence: 99%
“…Introducing montmorillonite-copper chloride into chitosan films can increase their tensile strength and elongation at break and also confer higher antibacterial activity against foodborne pathogens, further highlighting their use as a wound dressing to combat infections ( Nouri et al, 2018 ). Additionally, chitosan films containing human epidermal growth factors can protect against enzymatic hydrolysis and endocytosis and significantly accelerate the rate of wound healing in mice ( Umar et al, 2021 ). These antibacterial properties and regenerative effects of chitosan make it a suitable material for wound dressing.…”
Section: Drug Carriers Prepared Using Chitosan and Its Derivativesmentioning
confidence: 99%
“…Therefore, Umar et al concluded that water-soluble chitosan-containing hEGF-based liposomes can be considered a potential wound dressing for diabetic wound healing applications. 139 Human epidermal growth factor (hEGF) possesses excellent wound healing efficacy. The incorporation of liposomes as carriers and coatings protects hEGF from enzyme degradation, immune reactions and chemical reactions.…”
Section: Nanomaterial-based Therapies For Diabetic Foot Ulcersmentioning
confidence: 99%
“…Recent studies highlighted that modern dressings with natural active compounds or HEs can be an ideal delivery system in wound healing [ 115 , 116 ]. In addition, other studies describing the incorporation of lipid vesicles in modern dressings for wound healing have shown promising results [ 117 , 118 , 119 , 120 ]. Although, a thorough search of the relevant literature yielded only a limited number of studies in which VNs with PCs were included in polymeric dressings for wound healing [ 31 , 94 ].…”
Section: Topical Delivery Systems Containing Herbal Extractsmentioning
confidence: 99%